From Locked Out to Opting in: How the Cures Act Reshaped Medicare Advantage Utilization for Beneficiaries With End‐Stage Kidney Disease - Sih‐Ting Cai; Hailemichael Shone; Kosali Simon; Daniel Polsky (Health Services Research, 2026)
ABSTRACT Objective To describe how the characteristics of Medicare Advantage (MA) beneficiaries with end‐stage kidney disease (ESKD) changed after the 21st Century Cures Act expanded MA eligibility, and to document accompanying changes in utilization. Study Setting and Design The 2021 Cures Act opened MA to previously diagnosed ESKD patients. Prior to 2021, ESKD patients were ineligible for MA unless diagnosed while enrolled. This cross‐sectional descriptive study used 2017–2023 claims to compare enrollee characteristics before and after 2021, using interrupted time‐series analysis of monthly hospitalizations, emergency department visits, and outpatient visits. Data Sources and Analytic Sample Optum's de‐identified Clinformatics Data Mart Database (2017–2023) provided data on 216,205 MA beneficiaries with ESKD (359,172 beneficiary‐years). Principal Findings Post‐policy, enrollees were younger, had lower comorbidity burden and lower education attainment, and were more likely to report household incomes below $40,000. Hospitalization rates were lower immediately post‐policy by 0.013 per beneficiary‐month (6% relative decline; 95% CI, −0.022 to −0.003; p < 0.05). ED visits showed no immediate difference but increased over time. Outpatient visits remained largely stable. Conclusions Expanded MA eligibility was associated with a substantial shift in the ESKD MA case mix toward younger, relatively healthier, and more socioeconomically vulnerable beneficiaries. Utilization changes reflect these compositional differences.